Pemanfaatan Biochar sebagai Pembawa Rhizobium terhadap Pembentukan Bintil Akar dan Hasil Tanaman Kedelai (Glycine max L. Merril) - LUSIANA, NI PUTU NENA; SUWASTIKA, ANAK AGUNG NGURAH GEDE; ATMAJA, I WAYAN DANA; KESUMADEWI, ANAK AGUNG ISTRI (Agrotrop : Journal on Agriculture Science; Vol 11 No 2 (2021), 2021)
The Utilization of Biochar as a Carrier of Rhizobium for the formation of root nodules and Yield of Soybean ( Glycine max L. Merril) . This study aims to determine the effect of the type of raw materials and particle size of biochar as a Rhizobium carrier on the formation of nodules in soybean plants. This research was conducted from September to November 2020 at the Experimental Station and Laboratory of Soil and Environmental Sciences, Faculty of Agriculture, Udayana University. The research design used was a randomized block design with nested patterns with 2 factorials and 3 replications. The treatment factors consisted of B 1 = bamboo biochar, B 2 = albasia wood biochar, B 3 = corncob biochar, B 4 = young coconut skin biochar, P 1 = (0,15-0,50 mm), P 2 = (>0,50-1,68 mm), P 3 = (>1,68-3,36 mm). The parameters observed included effective nodule, nodule size, total bacterial population, ammonium, nitrate, and plant yield. The result of the analysis showed that the type of biochar raw materials had a very significant effect on the parameters of effective nodules, nodules size, total bacterial population and plant yield, but had no significant effect on soil chemical parameters. The treatment of biochar particle size had a very significant effect on the parameters of effective nodules, total bacterial population, and plant yield, and had a significant effect on the size of nodules, but had no significant effect on soil chemical parameters. The conclusion of this study is that the type of raw material for albasia wood biochar is effective as a Rhizobium carrier, which is indicated by the high number of effective nodules, nodules size and total bacterial population of 0,15-1,68 mm particles.